THE EFFECT OF WEIGHT PERCENTAGES OF CARBONYL IRON PARTICLES (CIP) ON THE PHYSICOCHEMICAL CHARACTERISTICS OF EPOXIDIZED NATURAL RUBBER-50 (ENR-50) BASED MAGNETORHEOLOGICAL ELASTOMERS (MRE) - AMARPALL SINGH, AJIT SINGH (IRC, 2020)
Magnetorheological materials are a type of smart material whose rheological properties can be manipulated within the presence of magnetic field. Magnetorheological Elastomers (MRE) and MR Fluids (MRF) are examples of materials under this class. Recently, MRF has been found to be not as reliable as expected with issues of fluid sedimentation, leakage, oxidation, and hard cake effect. This led to the re-emergence of MRE which does not possess the issues faced in MRF. MRE is a type of smart composite material comprised of an elastomer-based matrix, magnetic particles, and additives. To make MRE a viable alternative to MRF, MRE used solid matrix elastomer which can prevent all the issues that faced by MRF and the properties of magnetic particles such as low remnant, and high saturation magnetization make the MR effect in the rheological part is high. In order to possess those qualities, the magnetic particles must disperse efficiently throughout the matrix of the MRE